HUBUNGAN ANATOMI FISIOLOGI RAMBUT DENGAN KEMAMPUAN PENGERITINGAN RAMBUT KELAS XI KECANTIKAN DI SMKN 3 KOTA KEDIRI - Putri Ayu Oktafia; Octaverina Kecvara Pritasari; Novia Restu Windayani; Nia Kusstianti (Jurnal Tata Rias, 2025)
The low understanding of beauty students at SMKN 3 Kota Kediri regarding knowledge of hair anatomy and phishyology which is the basic of knowledge for practicing hair curling This study aims to determine the relationship between knowledge of hair anatomy and physiology and the ability to practice hair curling in grade XI students majoring in Beauty at SMKN 3 Kota Kediri. The research methot used is quantitative deskriptive with a correlational approach. The subjects of the study consisted of 30 students, with data collection through knowledge tests and performance/practice observation sheets. The result showed that the average knowledge of student was included in the very good category(87.33%), and the ability to practice was also classified as good with an avarage value of 83.5. The pearson correlation the showed significant relationship between knowledge of hair anatomy and physiology and the ability to practice curling with a correlation value of 0.685 (p < 0,05), Which indicates a strong level of relationship. In conclusion, the higher the students' knowledge of hair anatomy and physiology, the better their curling practice skills.